2021
DOI: 10.1097/jnn.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Face Validity of the Pain Numeric Rating Scale Among Healthcare Providers

Abstract: BACKGROUND: Healthcare providers (HCPs) use the numeric rating scale (NRS) under the assumption that it provides reliable information from which to make decisions regarding analgesic administration. METHODS: We explored the face validity of the NRS using a prospective single-blinded observational design. Pre and post NRS scores were obtained from HCPs who submerged their hand in a bucket of ice water (pain stimulus). RESULTS: Despite a consistent similar pain source, individual HCPs rated their pain very diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
2
Order By: Relevance
“…Using a numeric tool enhances patient-nurse communication, enabling patients to clearly express their pain intensity and the need for pain medication, which may or may not assist nurses in increasing their understanding of both the physiological and behavioral responses of patients to pain. 30 However, the percentage of nurses reporting the use of a numeric tool in this study was quite low, even lower than those reported in other settings. 17,25 Thus, encouraging the frequent use of numeric rating tools among nurses should be prioritized in future interventions.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Using a numeric tool enhances patient-nurse communication, enabling patients to clearly express their pain intensity and the need for pain medication, which may or may not assist nurses in increasing their understanding of both the physiological and behavioral responses of patients to pain. 30 However, the percentage of nurses reporting the use of a numeric tool in this study was quite low, even lower than those reported in other settings. 17,25 Thus, encouraging the frequent use of numeric rating tools among nurses should be prioritized in future interventions.…”
Section: Discussioncontrasting
confidence: 73%
“…It is understandable that nurses with a higher level of education and who are frequently reading pain resources have more knowledge regarding pain management and are more likely to implement it to their current practice. Using a numeric tool enhances patient-nurse communication, enabling patients to clearly express their pain intensity and the need for pain medication, which may or may not assist nurses in increasing their understanding of both the physiological and behavioral responses of patients to pain 30. However, the percentage of nurses reporting the use of a numeric tool in this study was quite low, even lower than those reported in other settings 17,25.…”
Section: Discussioncontrasting
confidence: 55%
“…24 Additional face validity can be provided in future studies wherein baseline knowledge (eg, years performing a neurological assessment) are included in data collection. 25 As previously noted, test-takers with varying levels of clinical experience in neuroscience were recruited to participate in the NAT. Construct validity is enhanced if the test is seen to measure the concept (knowledge of neurological assessment) that it is intended to measure.…”
Section: Discussionmentioning
confidence: 99%